2014
DOI: 10.1177/1534508414555705
|View full text |Cite
|
Sign up to set email alerts
|

Robust Regression for Slope Estimation in Curriculum-Based Measurement Progress Monitoring

Abstract: Although ordinary least-squares (OLS) regression has been identified as a preferred method to calculate rates of improvement for individual students during curriculum-based measurement (CBM) progress monitoring, OLS slope estimates are sensitive to the presence of extreme values. Robust estimators have been developed that are less biased by extreme values; however, the performance of robust estimators in the short data streams typical of CBM progress monitoring is unknown. The purpose of the current study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The discussant proposed that although they personally initially advocated against the use of data point rules, it may be time to explore ways in which level can be used for decisions. Indeed, substantial effort has been placed in refining trend estimation methods (e.g., Mercer, Lyons, Johnston, & Millhoff, 2014; Vannest, Parker, Davis, Soares, & Smith, 2012). While the findings of this study are not without limitations (see last section), they provide initial support for the notion of improving measures of level for the purposes of decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The discussant proposed that although they personally initially advocated against the use of data point rules, it may be time to explore ways in which level can be used for decisions. Indeed, substantial effort has been placed in refining trend estimation methods (e.g., Mercer, Lyons, Johnston, & Millhoff, 2014; Vannest, Parker, Davis, Soares, & Smith, 2012). While the findings of this study are not without limitations (see last section), they provide initial support for the notion of improving measures of level for the purposes of decision making.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of statistical methods have been used to estimate the trend of student data; until recently, there was evidence that ordinary least squares regression (OLSR) was the most accurate (Shinn, Good, & Stein, 1989). Although older trend estimation techniques may be replaced by new trend estimation techniques as they are disseminated (e.g., robust regression; Mercer, Lyons, Johnston, & Millhoff, 2015), the most common trend calculation of lines displayed on graphs today remains OLSR. This includes trend calculation within frequently used software systems such as AIMSweb, DIBELS, easyCBM, and FAST.…”
mentioning
confidence: 99%
“…Maximum Likelihood is another widely used estimator, although it has not been examined in the context of progress monitoring. Theil-Sen and Huber-M are the two slope estimators that are robust to the presence of outliers (e.g., Mercer et al, 2014). We excluded the other robust estimators-SMDM and Tukey's bisquare-from the simulation study because Mercer's, Lyons, Johnston and Millhoff (2014) study has already indicated that Huber-M can outperform the SMDM and Tukey's bisquare estimators when outliers are present in the progress monitoring data.…”
Section: Study 1: Monte Carlo Simulation Study Methodsmentioning
confidence: 99%
“…Most of the literature has focused on hand-fit trend lines (e.g., based on visual estimations) and linear regression methods, such as ordinary lest-squares (OLS) regression (Ardoin et al, 2013). More recently, the performance of various robust estimators, such as Huber M-estimator, Tukey's bisquare, and SMDM-estimation (i.e., an initial S-estimate, followed by an M-estimate, a Design Adaptive Scale estimate, and a final M-step; see Koller and Stahel, 2011 for more details), has been investigated in the context of CBM and progress monitoring measures (e.g., Mercer et al, 2014). Another robust estimation method, the Theil-Sen estimator, has been proposed to obtain more robust slope estimates from progress monitoring data (e.g., Vannest et al, 2012).…”
Section: Identification Of a Robust Slope Estimatementioning
confidence: 99%